How do you solve #5x4 +3 = 3#?
See the solution process below:
By signing up, you agree to our Terms of Service and Privacy Policy
To solve the equation ( 5x  4 + 3 = 3 ), you first subtract 3 from both sides to isolate the absolute value term, leaving ( 5x  4 = 0 ). Then, you solve the absolute value equation ( 5x  4 = 0 ) by setting the expression inside the absolute value bars equal to zero: ( 5x  4 = 0 ). Solving for x, you get ( x = \frac{4}{5} ).
By signing up, you agree to our Terms of Service and Privacy Policy
To solve the equation 5x  4 + 3 = 3:
 Subtract 3 from both sides of the equation:
5x  4 = 0.

Now, the absolute value equals zero, which means the expression inside the absolute value must be zero.

Solve the equation 5x  4 = 0:
5x  4 = 0 5x = 4 x = 4/5.
So, the solution to the equation 5x  4 + 3 = 3 is x = 4/5.
By signing up, you agree to our Terms of Service and Privacy Policy
When evaluating a onesided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a onesided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a onesided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a onesided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
 98% accuracy study help
 Covers math, physics, chemistry, biology, and more
 Stepbystep, indepth guides
 Readily available 24/7